STUDI KELAYAKAN BISNIS AYAM POTONG BERKAT ANUGRAH DENGAN ANALISIS VARIANS BIAYA PRODUKSI - Nur Maemuna Latahia; Muhammad Din; Munawarah (Publika Citra Media, 2026)
This study examines the feasibility of a broiler chicken farming business by applying variance cost analysis as an efficiency evaluation tool combined with financial indicators. A descriptive quantitative method was used through a case study of a medium-scale farm with 1,000 chickens per cycle. Data were obtained from interviews, observations, and financial records, and analyzed using variance techniques and financial feasibility indicators, including Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Profitability Index (PI). The results indicate an annual revenue of IDR 800,000,000 and a net profit of IDR 717,000,000, with a Payback Period of 1.67 months, an ARR of 156.38%, an NPV of IDR 2,617,994,116, and a PI of 27.18. Although cost variance analysis revealed unfavorable deviations in feed expenses, these did not significantly affect profitability. The study concludes that broiler farming is highly feasible and contributes theoretically by integrating business feasibility studies with cost accounting perspectives.